Aerosol Jet Print to Hybridize Circuitry of Electronic Devices - Bangshidhar Goswami (Journal of Power Electronics and Devices, 2021)
Gaseous to vapour has subsidized atomic provisions to set as molecular form on suit-in-addendum substrate. Decoration of molecular geometry is feasible to assess quantized computational differentiation. Aerosol generation of materials has applied new chemical reaction originated views into existing aerosol processes that improved clarification originated scheming as per theoretical basics, e.g., fabrication of quantum dots. Adoption of piezoelectric property for electronic devices from such crystals suggestion has been to integrate by forming such crystal structured, oxide films on substrates. Reasonable addendum of atomic arrangement on substrate has been subjected to process by usual thin film formation methods, e.g., spatter deposition, molecular beam epitaxy (MBE), chemical vapour deposition (CVD) and physical vapour deposition (PVD). Aerosol jet print has planned to print fine features to fabricate high performance flexible electronic devices. Low conductivity of nano-Pt ink has recovered from mixing synthetic nano-Pt particles, ethylene glycol with water and polyvinylpyrrolidone as adhesive additive and binder.